In Search of Authenticity: Humanist Weddings in the Polish Context - Rejowska, Agata (Religions, 2022)
The post-1989 transformation in Poland entailed not only institutional change, but also an ideational shift. Among other things, this ideational shift gave rise to a growing emphasis on individual autonomy, expressive values, and secularization, which has had an impact on the means of symbolic communication (e.g., rituals) and prepared the ground for the emergence of humanist marriage ceremonies in Poland. The secularization process has gradually undermined the taken-for-granted character of some religious practices, such as rites of passage. Additionally, with the increased focus on authenticity rather than on accuracy in the usage of some pre-stipulated scripts, social actors often tend to replace “ossified” meanings that are communicated through rituals with new meanings, which are perceived as more relevant. This paper sheds light on the issue of authenticity, which is an important category in studies of symbolic, ritual-like actions. Perceptions of authenticity were recurring themes during interviews conducted with couples who decided on a humanist wedding ceremony in Poland. Interviewees often asserted that they rejected the dominant Catholic rite because they perceived it as inauthentic.